Pengaruh Youtube Advertising Terhadap Minat Masyarakat Menjadi Pengguna My-BCA - Darryl Pratama Arman Hamzah; Veroni Palkar (Peneliti.net, 2023)
At this time the development of technology in human activities has grown rapidly, one of which is in the world of advertising. With the development of today's technology, the world of advertising is getting a big challenge. The emergence of new media is present in society that needs to be realized by anyone who carries out activities in the world of advertising, because in line with the development of advertising, new media will be created, one of which is using the YouTube site as an advertising medium. With the emergence of the YouTube site as an advertising medium, it is hoped that the public will become more interested in using the products or services offered. This journal was created to find out the effect of YouTube Advertising on public interest in using the products or services offered